AMERICAN MILITARY PRESENCE IN KYRGYZSTAN: PROBLEMS AND POSSIBLE REPERCUSSIONS (as of June 2007) - BONDARETS, Leonid (CENTRAL ASIA AND THE CAUCASUS, 2007)
The Manas airbase was set up in Kyrgyzstan in December 2001 on a temporary basis in connection with the counterterrorist operation launched by the U.S. and its allies in Afghanistan. America’s powerful information impact presented the terrorist attacks of 9/11 on New York and Washington as a challenge to the entire civilized world. Osama bin-Laden and al-Qa‘eda based on the Taliban-controlled territories of Afghanistan were appointed as the main culprits, which was accepted as a matter of fact even though there has never been and is still no convincing evidence of their involvement. Part of the expert community doubts that this terrorist structure was strong enough to carry out such a large-scale act of terror. The American side presented a note to the government of Kyrgyzstan on the status of the base and the American military deployed in the country, which was pushed through the parliament by the active efforts of those in the upper echelons of power who supported the project. From that time on,the military was to be treated as administrative and technical personnel of the U.S. embassy in full conformity with the Vienna Convention on Diplomatic Relations of 18 April, 1961. American aircraft and transportation means were exempt from control; the U.S. government, as well as military and civilian personnel, could move personal property, equipment, supplies, materiel, and technology in and out of the republic without inspection or control. They were exempt from customs dues, taxes, and any other types of payment. The U.S. authorities were allowed to use their own telecommunication systems and entire range of supporting radio frequencies. The Kyrgyz side preferred to keep away from conducting an in-depth legal analysis of the doc-ument or reviewing any possible political, economic, strategic, and other repercussions. This meant that from the very beginning the country’s leaders and the public were kept in the dark about the American military base and its activities. Washington skillfully exploited the Kyrgyz leaders’ tractability, lack of political will, and prag-matism, as well as the haste with which it decided to allow a foreign country to deploy its military contingent in the republic. Under the guise of the “counterterrorist” operation, the United States raised the issue of deploying its AWACS (airborne warning and control system) E-3 Sentry planes. The plans have not yet been buried: in 2005, NATO Early Warning and Control Force Commander Major Gen-eral Harry Winterberger publicly announced that in the near future NATO would have to either fly its AWACS planes from afar with refueling or set up bases nearby.1 In 2004, the base commanders and the republic’s Defense Ministry acting in strict secrecy signed an agreement on renting another stretch of land that extended the base area and its potential. The loss of its base in Uzbekistan spurred on America’s activities in Kyrgyzstan. President Bakiev, who came to power in 2005, seemed to accept America’s stronger military presence. His meetings with top American officials (one of them with the State Secretary behind closed doors), who made a habit of visiting the Kyrgyz Republic, ended in an agreement on the continued use of the Manas air-base signed by Condoleezza Rice and Kurmanbek Bakiev.2 This meant that the president of Kyrgyzstan unilaterally disavowed the Astana SCO Declaration that demanded that the “counterterrorist” coalition should specify the time period within which its military contingents would remain on the territories of SCO members.